2017
DOI: 10.1002/ejic.201700735
|View full text |Cite
|
Sign up to set email alerts
|

Towards Ultra‐Bright Gold Nanoclusters

Abstract: Fluorescence bioimaging is a non-invasive technique that permits to investigate living organism in real time with high tridimensional resolution. Properly engineered fluorescent (or photoluminescent) nanoparticles promise to surpass conventional fluorescent molecular probes as contrast agent. Photoluminescent semiconductor quantum dots show, for example, enhanced brightness and photostability. Concerns arising from the toxic metal content of quantum dots prompted the search for alternative inorganic nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 166 publications
0
53
0
Order By: Relevance
“…This decreases the nonradiative deactivation process and improves the stability of the AuNCs, leading to high QY values. 37 In addition, the presence of electron-rich cysteine residues on the concave surface of the protein scaffold can largely promote the photoluminescence of the protein-stabilized AuNCs. 36,38 The excited-state dynamics of the 4-AuNC was analyzed with timeresolved photoluminescence measurements (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This decreases the nonradiative deactivation process and improves the stability of the AuNCs, leading to high QY values. 37 In addition, the presence of electron-rich cysteine residues on the concave surface of the protein scaffold can largely promote the photoluminescence of the protein-stabilized AuNCs. 36,38 The excited-state dynamics of the 4-AuNC was analyzed with timeresolved photoluminescence measurements (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that Au (I)‐thiolate shell in the vicinity of Au (0) core contributes toward the intense luminescence through ligand‐to‐metal‐to‐metal charge transfer (LMMCT) mechanism . Therein, the metal–metal charge transfer originates from singlet state Au (0) core to triplet state (T1 or T2) of Au (I) shell, followed by the relaxation in the form of PL from T1 or T2 state of Au (I) shell to the highest occupied molecular orbital (HOMO) of Au (0) core.…”
Section: Resultsmentioning
confidence: 99%
“…Therein, the metal–metal charge transfer originates from singlet state Au (0) core to triplet state (T1 or T2) of Au (I) shell, followed by the relaxation in the form of PL from T1 or T2 state of Au (I) shell to the highest occupied molecular orbital (HOMO) of Au (0) core. The well‐defined nanocluster network through metal–ligand (Sn 2+ –GSH) interactions in these superstructural 3D architectures prohibits several nonradiative relaxation modes in GNCFs therefore, the strong luminescence primarily arises from the highly luminescent T1 state to Au (0) HOMO with an enhanced LMMCT relaxation mechanism . A slight PL blue shift may be due to the longer Au (I)⋅⋅⋅Au (I) distance in the nanocluster framework .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Dichiarante et al reported NIR-luminescent AuNCs bearing superfluorinated (SF) ligands with strong emission at 1050 nm with a quantum yield of 12% [77]. An extensive account of the PL of NCs is beyond the scope of this review and has been previously summarized in several reports [54,[78][79][80][81][82]. This review discusses an overview of the application of gold NCs in biosensing and bioimaging.…”
Section: Review Luminescent Gold Nanoclustersmentioning
confidence: 99%